EFFECT OF METHOD OF PLANTING AND PLANTLET DENSITY ON POTATO MINI-TUBER PRODUCTION - Sharma, Ashwani K; Kumar, Vinod; Venkatasalam, EP (Potato Journal, 2014)
An experiment was carried out at Central Potato Research Station, Kufri (Shimla) to find out the suitable method of planting the potato micro-plants with appropriate plant density for obtaining optimum number and size of mini-tubers. Three week old micro-plants of potato cultivar Kufri Himalini were planted in two different methods viz. flat bed and ridge-furrow system in combination with two plantlet densities, viz. 33 and 50 hills per m2, achieved by planting at two spacings viz. 30 x 10 cm and 20 x 10 cm respectively. Two plantlets were planted per hill. Higher number and yield of mini-tubers were obtained under flat bed (232.6 and 2.23 kg/m2 respectively) than ridge –furrow method (221.4 and 1.85 kg/m2 respectively). Higher plant density (20 x 10 cm) resulted in more number of mini-tubers (237.7/m2) than low density (216.2/m2). Plant density did not influence the yield of mini-tubers significantly. Planting at low density (30 x 10 cm) was better in improving the size of mini-tubers and reducing the proportion of